Learning Anatomical Structures of Dicot Plants using Jigsaw Puzzles among Middle School Students - Balamurugan, M. (Voices of Teachers and Teacher Educators, 2021)
Teachers must try different pedagogical strategies in their classrooms according to the nature and need of their learners. The major objective of the study is to assess the effectiveness of jigsaw puzzles in learning the transverse sections of a typical dicotyledon (dicot) stem and root, based on drawing and labelling skills among Class 8 students. The study adopted a single group pretest post-test experimental design with convenience sample of 11 boys and 14 girl students of Class 8 of a rural school in Tamil Nadu. The result indicated a significant positive effect of the jigsaw puzzle method in learning the transverse sections of a typical dicot stem and root based on drawing and labelling skills. Boys and girls did not differ significantly in their performance before and after the intervention in both the drawing and labelling skills. The researcher recommended the adoption of the jigsaw puzzle method in learning the concepts of anatomical structures at high and higher secondary level.